NORMATIFITAS HUKUM ISLAM DAN HISTORISITAS SOSIAL DALAM TAUTAN HARMONISASI PEMAHAMAN - Firdaus Achmad (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
As a religion that contains universal values, Islam offers well organized, balanced, and meaningful life. This offer is strengthened by role of Al-Qur’an and Al-Hadits as main sources of Islamic teaching.These sources comprise normative rules which are believed to beguidance in the process of living and finding the meaning of life.The existence of Al-Qur’an constitutes idealization of universe within well-organized life of human being. Meanwhile, Al-Hadits offers interpretation of language used by God in Al-Qu’an. In other word, Al-Qur’an more tends to be idealistic while Al-Hadits more tends to be realistic. As the interpretation of Al-Qur’an, Al-Hadits is trapped inspace and time because its interpretation is full of modern society consideration. This consideration then brings some problems when the result of the interpretation passes space and time which are to come. The difference in factual phenomenon emergesas the consequence of manner pattern towards life movement, future and past. It needs to fit the formulation of rule based on modern values. It suggests that Al-Qur’an and Al-Hadits should prioritize harmonic values in the combination of normative demand and life history.